Enhancing Students’ Learning Interest in Integrated Science and Social Studies Through Contextual Interactive Animation Videos - Nirwana, Intan; Imran, Imran; Aulia, Nisa (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study investigates the effectiveness of contextual interactive animation videos in enhancing fourth-grade students’ learning interest in Integrated Science and Social Studies (IPAS). Employing Classroom Action Research (CAR) based on the Kemmis and McTaggart cyclical model, the study was conducted over two cycles involving fourth-grade students during the 2025/2026 academic year. Data were collected through triangulation of structured observations, Likert-scale questionnaires, semi-structured interviews, and documentation. This study involved the entire student population at SD Islam As’ad Olak Kemang in the 2025/2026 academic year and designated the fourth-grade class as the sample through purposive sampling. Quantitative data were analyzed using percentage techniques, while qualitative data were interpreted descriptively. Baseline findings indicated substantial student disengagement, largely driven by the dominance of conventional lecture methods and the limitations of damaged teaching aids. Following the intervention, students’ learning interest improved markedly across cycles, with the most pronounced gains observed in active participation and self-confidence alongside notable improvements in teacher instructional quality. The integration of contextual interactive animation successfully facilitated a shift toward Guided-Discovery learning and revealed an “Efficiency Paradox,” whereby digital media effectively compensated for inadequate physical infrastructure. These findings position contextual interactive animation as a scalable and compensatory pedagogical innovation for resource-constrained primary classrooms.